KEANEKARAGAMAN SERANGGA PERMUKAAN TANAH DI KAWASAN BUKIT GATAN KABUPATEN MUSI RAWAS - Dina Setiawati; Yunita Wardianti; Mareta Widiya (LP4MK STKIP PGRI Lubuklinggau, 2021)
This study aims to determine the diversity of soil surface insects, in the Bukit Gatan area, Musi Rawas Regency. This research is a qualitative descriptive study using a pitfall trap and using a random sampling method. The results showed that the types of ground surface insects contained 3 orders, 5 families and 10 species.The results of the analysis of the ecological index of soil surface insects in the Gatan hill area, Musi Rawas Regency, namely the diversity index (H') 1.241 in the low category, Evennes index (E') 0.64 in the medium category, and the dominance index (C)0.277 in the medium category.The abiotic factors in the Bukit Gatan area, Musi Rawas Regency at the research site are the average air temperature 29℃, average soil pH 6.5, and average soil moisture 85.3%.Diversity of soil surface insects in the Bukit Gatan area, Musi Rawas Regency is in the low category.